PENINGKATAN KEMAMPUAN GURU DALAM MENENTUKAN KRITERIA KETUNTASAN MINIMAL (KKM) MELALUI WORKSHOP DI UPTD SDN BANDA SOLEH 1 KECAMATAN KOKOP KABUPATEN BANGKALAN TAHUN 2019 - Mohammad Yusuf (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The role of teacher in improving the quality of society service is making the students able to learn quietly, peacefully and joyfully. Therefore, teachers should also get founding. One of founding for teachers is self-development as to determine the standard Minimum Passing Criteria known as KKM (Kriteria Ketuntasan Minimal). It is because the teachers have not been capable enough to make KKM. Coaching is carried out including workshops. The level of success includes observing mental readiness, material, and teacher attendance. The results showed an increase in the ability of teachers to determine Minimum Completion Criteria (KKM) through workshops in the UPTD of SDN Banda Soleh 1. This was evidenced by 4 out of 12 people who were mentally prepared in the first cycle or 33% experienced an increase in the cycle II reached 92% or 11 of 12 teachers. Furthermore, in the first cycle there were 5 out of 12 people not ready for material or 42%, but in cycle II the teachers could bring material up to 92% or 11 of 12 people according to the criteria. Whereas in terms of attendance, the teacher was still present all in the implementation of coaching in the UPTD of Banda Soleh 1 Elementary School in Kokop District.